2022
DOI: 10.1111/ddi.13536
|View full text |Cite
|
Sign up to set email alerts
|

Finding what you don’t know: Testing SDM methods for poorly known species

Abstract: Aim: A limitation of species distribution models (SDMs) is that species with low sample sizes are difficult to model. Yet, it is often important to know the habitat associations of poorly known species to guide conservation efforts. Techniques have been proposed for modelling species' distributions from a few records, but their performance relative to one another has not been compared. Because these models are built and evaluated with small data sets, sampling error could cause severely biased sampling in envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Since several studies (e.g., Escobar, Qiao, Cabello, & Peterson, 2018; Pearson et al, 2006) have shown that the accuracy of SDMs is distorted by the quality of data (Fernandes, Scherrer, & Guisan, 2019) and small sample sizes, SDMs were built only for species with >15 occurrence data points following van Proosdij, Sosef, Wieringa, and Raes (2016). For species with <20 locality points, species‐specific model settings were used (Radomski et al, 2022). Of the 5510 initial specimen locality data collated, only 3576 specimens representing 101 GCFR species were ultimately used for SDM development (Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since several studies (e.g., Escobar, Qiao, Cabello, & Peterson, 2018; Pearson et al, 2006) have shown that the accuracy of SDMs is distorted by the quality of data (Fernandes, Scherrer, & Guisan, 2019) and small sample sizes, SDMs were built only for species with >15 occurrence data points following van Proosdij, Sosef, Wieringa, and Raes (2016). For species with <20 locality points, species‐specific model settings were used (Radomski et al, 2022). Of the 5510 initial specimen locality data collated, only 3576 specimens representing 101 GCFR species were ultimately used for SDM development (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…There are several debates regarding the limitations of the use of AUC to assess model performance (e.g., Escobar et al, 2018). However, many authors argued that the use of MaxEnt model for the SDM takes such limitations into consideration (e.g., Galante et al, 2018; Radomski et al, 2022; Sheth et al, 2014) and AUC can be used if a threshold of >0.5 via jack‐knifing is adopted (Escobar, Qiao, Cabello, & Peterson, 2018; Hijmans, 2019). Further, for improved model performance, we employed a null model test (van Proosdij et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Both the evaluation of bivariate models (Breiner et al . 2015) and the final ensemble were done using the Boyce Index (Radomski et al . 2022).…”
Section: Methodsmentioning
confidence: 99%
“…We then built a final ensemble prediction averaging across the selected models. Both the evaluation of bivariate models (Breiner et al 2015) and the final ensemble were done using the Boyce Index (Radomski et al 2022). We then projected the model under the climate and LULC change scenarios.…”
Section: Model Building and Validationmentioning
confidence: 99%
“…To construct the species distribution model of greater mouse-deer, we applied the maximum entropy algorithm [53] using Maxent 3.4.1 software [54]. This method is recommended for generating species distribution models when sample sizes or occurrence records are small [55], and its popularity has increased over the past decade owing to the robust distribution estimates obtained [56]. The "kuenm" package [57] in R 4.2.0 [58] was used to select the model used to estimate habitat suitability in a study area.…”
Section: Modeling Species Distributionmentioning
confidence: 99%